Grading Of Severity Of Atopic Dermatitis In North Indian Children - Dhar Sandipan; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 1995)
Severity of atopic dermatitis (AD) was assessed in 80 children (up to12 years), 48 boys and 32 girls, using grading system as suggested by Rajka and Langeland. Thirty-three (41.25%), 44 (55%) and 3(3.75%) patients had mid, moderate and severe diseases respectively. Mean severity scores were 3.5,5.7 and 8.3 respectively in these 3 groups. Boys had a more Severe disease than girls. Patients with early (0-3 months) and late onset (6-9 years) of disease had maximum severity, mean severity scores being 5 and 5.3 respectively. Patients with moderate AD had a more prolonged course than those with mild disease. Family history of atopy had no impact on the severity of AD, although personal history of atopy was common in patients with moderate AD. Face was equally affected in mild disease group.